Produção de etanol empregando leveduras convencionais e termotolerantes - Vargas, Nayana Simon de (2017)
To attend the increase in Brazilian ethanol consumption and exportation, and also to comply with the goals established in the COP 21 and Quioto protocol, it will be necessary to increase the ethanol production in the next years. This purpouse can be achieved by using new yeast strains, new raw materials, and new extraction techniques. Thus, the objeticve of this work was evaluated the ethanol production by Kluyveromyces marxianus, a thermotolerant yeast, and its remotion by carbon dioxide stripping throughout the fermentation. In this work, fermentation experiments were carried out in agitated flasks in temperature range from 36 to 44 ºC using K. marxianus and in the range from 34 to 40 oC using Saccharomyces cereviae (commercial and industrial strains) to compare the performance of both yeasts. Thermotholerant yeast was evaluated using a medium composed by sweet sorghum and molasses in experiments carried out in agitated flasks at 40 oC. Assays with K. marxianus were carried out in a bioreactor (2 L) operated in batch mode and using carbon dioxide stripping (specific flow rates of 1.0, 1.5 and 2.5 vvm) . For all fermentation experiments the main kinetic parameters and yields were calculated. The fermentation process was modeled using Levenspiel kinetic. Stripping process was also modeled considering a first order kinetic. The model parameters were estimated by genetic optimization algorithm. Fermentations carried out at 40 oC with K. marxianus yeast exhibit a similar performance to that obtained in most Brazilian mills. Sweet sorghum demonstrated to be a promising raw material and the thermotolerant strain was able to consume all the sugars present in the broth. In the stripping experiments it was observed an increase in the value of the ethanol volumetric productivity. The higher value (9.02 gE/L∙h) was obtained in the experiment carried out at 1.0 vvm. The proposed mathematical model was able to adequately describe the fermentation processes.